Urgensi Pembelajaran Bahasa Inggris pada Anak Usia Dini - Adah Puadah (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah UI BBC, 2024)
The aims of the study are to accommodate and figure out parents’ opinion about learning English in Early Chilhood Education. Qualitative reserach design was used to this study. Survey and interview were used in gaining primer data and observation is used to triangulate this study. Sixty parents (woman) were sample for this study. They were asked to fill the survey given by the researcher and answering some questions in interview session. The results of study show that almost ninety percents of the parents strongly agree and feel important to implement learning English in Early Childhood Education. They added learning English in the beginning perioed will help children to improve their English skill maximally. Therefore, the implication of the study is to give confirmation for all of management PAUD to be aware and tries to give learning service based on trend and society need speacially learning English.